Criminal Law Policy of Counteracting Crimes against Property - Irina G. Ragozina (Сибирское юридическое обозрение, 2016)
The article is devoted to the current state of the criminal law policy of counteracting crimes against property. The focus is made on its main directions, such as law-making and law enforcement. The issues of unification and differentiation of criminal liability for crimes against property are under study. The author draws the conclusion that no unified approach is used when producing criminal law prohibitions criminalizing encroachment on someone else's property.